Edinburgh breast education campaign on breast cancer and breast self-examination: was it worth while?. Issue 4 (December 1986) - Roberts, M M; Robinson, S E; French, K; Proudfoot, A; Talbot, H; Elton, R A
Abstract : A health education campaign was carried out at the start of a large trial of screening for breast cancer in Edinburgh. After preliminary studies the campaign concentrated on talks to small groups of women by specially trained health visitors. Over a year, 12, 000 women attended. Systematic evaluation after 12 months showed that selected women who heard the talks were more knowledgeable about breast cancer, and a random sample of women in Edinburgh had a small but significant improvement in knowledge compared with women in Aberdeen. However, the random sample did not report an increase in the practice of breast self-examination (BSE) and there was no increase in workload for general practitioners. It is suggested that BSE is more likely to be accepted if combined with a physical examination.